Strategi pengendalian diri dalam perspektif Al-Qur’an Surat Al-Hujurat ayat 12 - Rohman, Ujang; Ismail, Shalahudin; Savela, Reva (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Surah Al-Hujurat verse 12 provides guidance on self-control in dealing with negative assumptions and gossiping behavior in social interactions. This verse emphasizes the importance of avoiding negative assumptions, avoiding seeking the faults of others, and prohibiting backbiting. Self-control in dealing with negative assumptions and gossiping behavior includes controlling one’s attitude and speech, as well as awareness of the existence of Allah. Mutual respect and acceptance that humans are not perfect form the basis for this self-control. In conclusion, Surah Al-Hujurat verse 12 teaches that self-control against negative assumptions and gossiping is the key to positive and loving social relationships, reflecting Islamic values in interacting with others.